Antecedents to the disclosure of a stigmatized national identity in cross‑national work settings - Nyobe, Sara (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
International Business (IB) and management studies have neglected giving needed attention to interactions of individuals with stigmatized national identities with overseas clients. This leaves uncertainty about the antecedents that lead these individuals to disclose their national identity to foreign clients or keep it hidden. Drawing on Social Identity Theory (SIT) and Stigma Theory, this comparative case study of two Tunisia-based call centers serving western markets indicates that identity-related choices depend more on skills and experiences individuals possess than on how they relate to each other. The study contributes to both IB and management studies by completing the existing definition of SIT and offering solutions regarding how to address stigma in IB.